SK 188 SEBAGAI PEMICU PERLAWANAN MASYARAKAT TERHADAP PERTAMBANGAN PASIR BESI DI KECAMATAN WERA - Aidin (STKIP Al-Amin Dompu, 2022)
The community's rejection of mining was caused by the issuance of a Regional Government Decree of the Bima Regency in relation to issuing a Decree (SK) with the number. 188/2010, to PT. Jagad Mahesa Karya, which is engaged in mining. The research method is qualitative. The result of the research is that the community's rejection of mining is influenced by several factors. First, the policy issued by the Government in granting exploitation permits to Jagad Mahesa Karya companies engaged in iron sand mining. Because for the community the presence of mining will not be able to change the way of life of the community, it will make the community poorer. The two iron sand mines in Wera District have not been accepted by the community, because the community's understanding of mining is still minimal. Third, the Regional Government rules violate Regional Regulation (PERDA) No. 5 of 2008, that in the PERDA there is no discussion on iron sand mining. in the regional regulations related to agriculture, tourism, fisheries and plantations. Fourth, there is no clear regulation regarding environmental impact analysis in the management of iron sand mining in Wera District.